2019
DOI: 10.3389/fenrg.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Microbiological Characterization of Bioanode Communities Exhibiting Variable Levels of Startup Activity

Abstract: Microbial electrochemical technologies (METs) require the establishment of anode biofilms to generate electrical current. The factors driving bioanode formation and their variability during startup remain unclear, leading to a lack of effective strategies to initiate larger-scale systems. Accordingly, our objective was to characterize the electrochemical properties and microbial community structure of a large set of replicate bioanodes during their first cycle of current generation. To do this, we operated eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…enrichment biofilms differ from mature biofilms. Consequently, investigations on the physiological development of electroactive biofilms should be intensified for, e.g., optimizing organic load during start-up phase of MET [48,49]. Furthermore, microbial community analysis of the bulk liquid [73] as well as headspace gas analysis will be helpful for assessing and quantifying competitive microbial processes, especially in Geobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…enrichment biofilms differ from mature biofilms. Consequently, investigations on the physiological development of electroactive biofilms should be intensified for, e.g., optimizing organic load during start-up phase of MET [48,49]. Furthermore, microbial community analysis of the bulk liquid [73] as well as headspace gas analysis will be helpful for assessing and quantifying competitive microbial processes, especially in Geobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…avoiding the current erratic behavior thereof [48][49][50]. Therefore, a study combining timeresolved substrate analysis during batch cultivation with electrochemical measurements of Geobacter spp.…”
Section: Plos Onementioning
confidence: 99%
“…This handicap was already identified in 2009 by Larrosa et al, proposing a minimum of four replicates for MFC experiments for leveling off variation in performance. In the last decade, this experimental variability was demonstrated in various single studies of different labs, e.g., Koch et al and Ortiz-Medina et al 3,4 Recently, the unreliability of biofilm anodes was confirmed in a global ring test. 5 In essence, stochasticity in the formation of biofilm anodes, especially for complex substrates and inoculums, results in an almost unpredictable performance thereof.…”
mentioning
confidence: 97%